Além da traição: Manoel Jover Teles e o comunismo no Brasil do século XX - Silveira, Éder da Silva (Universidade do Vale do Rio dos Sinos, 2013)
The research analyzes, from a Manuel Jover Teles historical biography construction, this militant and Brazilian communist leader life trajetory in the political field and issues related to the notion of Betrayal in communist culture. The work includes a reflexive analysis of processes and barely noticeable relationships in structural studies on the Republican Brazil history, particularly about communism and communist dissent. Sensitive issues of the recent history of communism in Brazil, as resentment and Betrayal, are analyzed in and from Jover Teles history.
Keywords: História Brasil; Comunismo; História; Brasil; Traição; ACCNPQ::Ciências Humanas::História